Pengaruh Internet Banking, Risiko Kredit dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017 - 2019 - Siska Wulandari; Nunuk Novitasari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study is to view, analyze, and test the relationship between internet banking and bank performance. The banks used are those listed on the Indonesia Stock Exchange (IDX) in 2019. The method is Multiple Linear Regression by adding two control variables, namely credit risk measured by the NPL ratio and company size measured by the log of total assets with ROA as a measure of the Bank's performance. The findings of this study indicate that internet banking has a positive effect on ROA. The use of internet banking can increase ROA. Commercial banks play a big role in changing (growing) the economy of each country. NPL has a negative and significant effect on ROA. This means that it illustrates an inverse comparison between credit risk and bank performance. If credit risk increases, it will reduce ROA. Company size has a negative and insignificant effect on ROA, it is suspected that the cause is that large assets are not necessarily supported by good management. Company size cannot be used as a guarantee that large companies have good performance, large companies, of course, the costs incurred are also large. resulting in lowering ROA.